2021
DOI: 10.3390/app11020846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Impact Weight-Bearing Exercise on Bone Mineral Density and Bone Metabolism in Middle-Aged Premenopausal Women: A Randomized Controlled Trial

Abstract: This study examined the effects of high-impact weight-bearing exercise on bone mineral density (BMD) and bone metabolic markers in middle-aged premenopausal women. Forty middle-aged premenopausal women were initially enrolled, but thirty-one participants (40.34 ± 3.69 years) completed in the study. The subjects were randomly divided into two groups including the high-impact weight-bearing exercise group (HWE, n = 14) and control group (CON, n = 17). The HWE group participated in the exercise for 50 min a day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…During menopause, higher body weight seems to decelerate bone loss [34]. The higher BMD in obese subjects, reported by many authors, is attributable to the mechanical effect of body weight on bone [20,[35][36][37][38]. The scientific literature shows how weight bearing increases bone density by acting also at the cellular level [39].…”
Section: Obesity and Mineral Bone Densitymentioning
confidence: 99%
“…During menopause, higher body weight seems to decelerate bone loss [34]. The higher BMD in obese subjects, reported by many authors, is attributable to the mechanical effect of body weight on bone [20,[35][36][37][38]. The scientific literature shows how weight bearing increases bone density by acting also at the cellular level [39].…”
Section: Obesity and Mineral Bone Densitymentioning
confidence: 99%
“…Prevention of the onset of osteoporosis would also be important to characterize the effects of high-impact exercise on middle-aged, pre-menopausal women. Kim et al [11] performed this type of study and showed that a physical activity program (intensity set at 60-80% of maximal heart rate) reduces age-associated changes in bone markers, although it does not increase the bone mineral density.…”
Section: Effects Of High-impact Weight-bearing Exercise On Bone Mineral Density and Bone Metabolism In Middle-aged Premenopausal Women: Amentioning
confidence: 99%
“…Sixteen papers have been published, which are briefly described below. They range from mobile applications in physiotherapy to changes in bioactive lipids in half-marathoners [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several alterations in the gut microbiome can lead to obesity, by modulating metabolic pathways and eating behaviors of the host through GBA. For obese patients, their body weight has the mechanical effect of body weight on bone which acts at the cellular level to increase bone mineral density (Bisaccia et al, 2021, Kim et al, 2021. Some experiments have shown that osteocytes are particularly sensitive to biomechanical stress.…”
Section: Introductionmentioning
confidence: 99%